Public attitudes regarding large-scale solar energy development in the U.S. (August 2015) - Carlisle, Juliet E.; Kane, Stephanie L.; Solan, David; Bowman, Madelaine; Joe, Jeffrey C.
Abstract: Using data collected from both a National sample as well as an oversample in U.S. Southwest, we examine public attitudes toward the construction of utility-scale solar facilities in the U.S. as well as development in one's own county. Our multivariate analyses assess demographic and socio-psychological factors as well as context in terms of proximity of proposed project by considering the effect of predictors for respondents living in the Southwest versus those from a National sample. We find that the predictors, and impact of the predictors, related to support and opposition to solar development vary in terms of psychological and physical distance. Overall, for respondents living in the U.S. Southwest we find that environmentalism, belief that developers receive too many incentives, and trust in project developers to be significantly related to support and opposition to solar development, in general. When Southwest respondents consider large-scale solar development in their county, the influence of these variables changes so that property value, race, and age only yield influence. Differential effects occur for respondents of our National sample. We believe our findings to be relevant for those outside the U.S. due to the considerable growth PV solar has experienced in the last decade, especially in China, Japan, Germany, and the U.S.